Performance of Multiuser MIMO-SWIPT Layered Transmission Systems - Ozyurt, Serdar; Kucur, Oğuz (IEEE, 2023)
In this study, the performance of multiuser multi-input multi-output (MIMO) simultaneous wireless information and power transfer (SWIPT) layered transmission system is investigated under downlink scenario. For the first time in the literature, each user is assumed to simultaneously perform energy harvesting (EH) and information decoding (ID) under the MIMO-SWIPT layered transmission system. To this end, antenna switching technique is used at the receivers and the idea that while a set of receive antennas is reserved for EH, the remaining antennas are exploited for ID is adopted. In addition, power-domain non-orthogonal multiple access is utilized for multiuser multiple access process. A number of numerical results are presented on the amount of harvested energy, attained data rate, and outage probability.
31st IEEE Conference on Signal Processing and Communications Applications (SIU) -- JUL 05-08, 2023 -- Istanbul Tech Univ, Ayazaga Campus, Istanbul, TURKEY
Keywords: Simultaneous wireless information and power transfer; multi-input multi-output; non-orthogonal multiple access; downlink